2016
DOI: 10.1007/s10195-016-0402-2
|View full text |Cite
|
Sign up to set email alerts
|

Medial unicompartmental knee arthroplasty in the ACL-deficient knee

Abstract: Symptomatic osteoarthritis (OA) of the knee develops often in association with anterior cruciate ligament (ACL) deficiency. Two distinct pathologies should be recognised while considering treatment options in patients with end-stage medial compartment OA and ACL deficiency. Patients with primary ACL deficiency (usually traumatic ACL rupture) can develop secondary OA (typically presenting with symptoms of instability and pain) and these patients are typically young and active. Patients with primary end stage me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
44
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(46 citation statements)
references
References 32 publications
(54 reference statements)
0
44
0
2
Order By: Relevance
“…The first reports highlighted a higher incidence of complications following UKA surgery in ACL-deficient knees, in terms of tibial loosening and a higher revision rate 51 52. Mancuso et al 53 summarised the evidence in the literature concerning ACL deficiency in UKA surgery; they concluded that combining ACL reconstruction and UKA is the preferred treatment option for patients with ACL deficiency and bone-on-bone medial OA. Simultaneous or staged ACL reconstruction tends to provide superior outcomes, in particular in younger and more active patients.…”
Section: Current State Of the Artmentioning
confidence: 99%
See 1 more Smart Citation
“…The first reports highlighted a higher incidence of complications following UKA surgery in ACL-deficient knees, in terms of tibial loosening and a higher revision rate 51 52. Mancuso et al 53 summarised the evidence in the literature concerning ACL deficiency in UKA surgery; they concluded that combining ACL reconstruction and UKA is the preferred treatment option for patients with ACL deficiency and bone-on-bone medial OA. Simultaneous or staged ACL reconstruction tends to provide superior outcomes, in particular in younger and more active patients.…”
Section: Current State Of the Artmentioning
confidence: 99%
“…Simultaneous or staged ACL reconstruction tends to provide superior outcomes, in particular in younger and more active patients. In the elderly, UKA without ACL reconstruction seems to be a reasonable and attractive option if a fixed-bearing design is used, but careful patient selection is necessary 53. The literature shows no statistical difference between survival rates of UKAs implanted in ACL-deficient and ACL-intact knees 54.…”
Section: Current State Of the Artmentioning
confidence: 99%
“…In their review of the literature, Mancuso et al 66 devised a treatment algorithm based on joint stability, patient age and joint function requested by patients. According to the algorithm, the preferred procedure for young patients with ACL rupture and end-stage medial compartment OA is the combined procedure performed in a single surgical step.…”
Section: Review Of the Literaturementioning
confidence: 99%
“…In their systematic review of the literature, Mancuso et al 66 compared the type and rate of complications after combined UKA and ACL reconstruction surgery versus UKA alone for ACL-deficient knees. A significantly higher failure rate was noted in patients who did not undergo ACL reconstruction as compared with those who received a combined procedure (19/154 vs 4/108).…”
Section: Complicationsmentioning
confidence: 99%
See 1 more Smart Citation